Pertanggung Jawaban Pidana Kasus Korupsi oleh Direktur PT Beringin Bangun Utama dalam Surat Putusan No. 64/Pid.Sus/Tpk/2016/Pn.Bgl - Ronald Hasudungan Sianturi; Yuli Rosanti Sartika Sitompul; Rima Ara Rizki (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the criminal responsibility for corruption cases by the director of PT Beringin Bangun Utama (Study of Decision Number 64/Pid.Sus/TPK/2016/PN.Bgl). The problem is focused on the form of losses suffered by the state, penalties and criminal responsibility for corruption cases by the director of PT Beringin Bangun Utama. In order to approach the problem, normative juridical theory is used as a reference. The data were collected through literature studies, decisions and previous research and then analyzed qualitatively. This study concludes that losses to the state caused by the actions of the director of PT Beringin Bangun Utama in the financial and economic sectors are elements that are included in the category of a criminal act of corruption. The legal action given is in the form of disbanding the corporation, confiscation of documents and being threatened with crime in accordance with Article 2 Paragraph (1) in conjunction with Article 20 in conjunction with Article 18 of Law no. 31 of 1999 concerning the Eradication of Corruption Crimes which has been amended by Law no. 20 of 2001 concerning Amendments to Law No. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption. And in the second indictment where the defendant was threatened with a crime in Article 3 in conjunction with Article 6 in conjunction with Article 7 of Law no. 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering.